Gambling-think - Lim, MSM (2013)
Background: Cognitive perspectives suggest that gambling-related cognitive (GRC) biases contribute to the development and maintenance of gambling problems. Evidence has since accumulated to support these claims: GRCs tend to be stronger amongst problems (and pathological) gamblers, and can be effective therapeutic targets of talking treatments. However a richer account of how GRCs are conditioned by gamblers' game and group interactions might enhance their explanatory power and therapeutic value. Methods: Here, I present the results of an extended programme of research involving: (i) laboratory-based experiments on action-based expressions of illusions of control (IOC; Studies 1-4) and value learning when making decisions under uncertainty (Study 5); (ii) online surveys of Chinese gamblers' participation patterns and beliefs in luck (Study 6); and finally, (iii) qualitative interviews of treatment-seeking professional footballers in the United Kingdom (Study 7). Results: Studies 1-2 demonstrated that (non-problematic) gamblers displayed IOC biases by rolling a simulated die for longer when attempting to hit targets with larger prizes and numerical values. These action-based expressions of IOC were facilitated by congruent target numbers and prizes (Study 3), and heightened competition with gambling co-actors (Study 4). Additionally, computational models of gamblers' choices in Study 5 showed that self-report GRCs, and impulsivity, weaken gamblers' ability to learn the value of competing game options. Next, Study 6 reported that Chinese gamblers' GRCs were related to a broader range of gambling activities, and self-report IOCs mediated the association between beliefs in luck and the number of reported gambling problems. Finally, Study 7 found that social pressures, high income, and work-related frustrations precipitated problematic gambling involvement in treatment-seeking footballers. Discussion: Overall, the results suggest that a richer account of GRCs can be achieved by considering the sensorimotor and sociocultural contexts of gamblers. My thesis concludes with a discussion of GRCs within more recent theoretical developments of the embodied and social cognitions paradigms.